Determination and validation of ketoprofen, pantoprazole and valsartan together in human plasma by high performance liquid chromatography - (:unkn) unknown (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2006)
A rapid and specific high-performance liquid chromatographic method was developed and validated for the simultaneous determination of ketoprofen, valsartan and pantoprazole in human plasma. Chromatographic separation of ketoprofen, valsartan and pantoprazole was performed using a Chromasil C-18 column (250 mm x 4.6 mm i.d., 5 mu m particle size). The mobile phase consisted of a mixture of 0.02 M sodium dihydrogen phosphate buffer (pH 3.15) and acetonitrile (58:42, v/v) pumped through the chromatographic system at a flow rate of 1 mL (.) min(-1). The Diode Array detector was operated at 225 and 272 nm. Rofecoxib was used as an internal standard. Sample treatment procedure consisted of deproteinisation with acetonitrile-methanol (50:50 v/v). Analytical recoveries were in the range of 79.00-118.00% of nominal values of valsartan, ketoprofen and pantoprazole. The method was reproducible and accurate with lower limits of quantification 250 mu g (.) L-1 for pantoprazole and 500 mu g (.) L-1 for ketoprofen and valsartan. This method was relatively easy to perform and allows simultaneous determination of these three drugs in plasma at nanogram levels.
Keywords: ROFECOXIB; HPLC; LC